A Translation Analysis Of English Interrogative Sentence In Ender's Game Novel By Orson Scott Card - Susilo, Heri Budi; , Dr. Dwi Haryanti, M.Hum; , Aryati Prasetyarini, S.Pd, M.Pd (2014)
This study aims at analyzing the interrogative sentences found in Ender's Game novel and its translation. This research applies descriptive qualitative method. The objectives are to describe the translation variations of interrogative sentences and to describe the translation accuracy of interrogative sentences in Ender's Game novel. The data are interrogative sentences found in Ender's Game novel and its translation. The data were collected by using content analysis and interview. The results of the research shows that, firstly, there are translation variation of interrogative sentences. 1) Yes-no questions are translated into three types of interrogative sentence, namely, interrogative sentence by using Apa, by adding Suffix-kah and into declarative question. 2) Tag questions are translated into interrogative sentence by using Kan or Bukan, by using Suffix-kah and into declarative question. 3) Interrogative-word questions are translated into several types. Interrogative word question 'What' is translated into interrogative sentence by using Apa, Bagaimana and Mengapa. Interrogative-word question 'Who' is translated into Siapa. Interrogative-word question 'Which' is translated into interrogative sentence by using Mana (Yang mana, Kemana or Dimana). Interrogative-word question 'Where' is translated into Kemana or Dimana. Interrogative-word question 'When' is translated into Kapan. Interrogative-word question 'Why' is translated into Mengapa and (untuk) + Apa. Interrogative-word question 'How' into Bagaimana and Berapa. Second, the translation accuracy is categorized as accurate, less accurate and inaccurate translation. The assessment of translation accuracy show that 391 data or 79.8% data are accurate, 89 data or 18.2% data are less accurate and 10 data or 2% data are inaccurate. The translation accuracy of interrogative sentence in Ender's Game novel is categorized as high accurate translation. Keywords: translation.